STATUS OF SUSTAINABILITY OF SONDONG FISHERIES BASED ON ECOLOGICAL, SOCIAL AND TECHNOLOGICAL ASPECTS AT THE THE TECHNICAL IMPLEMENTING UNIT (UPT) PORT FISHERIES OF RIAU PROVINCE - Wahyuni L, Mutia; Zain, Jonny; Bustari, Bustari (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2022)
Abstract Sustainable fisheries management for sondong fishing gear needs information support so that sustainable management goals can be realized. Its management includes ecological, social and technological dimensions. The purpose of this study was to determine the sustainability status of the sondong fishery in the Technical Implementation Unit (UPT) of the Fisheries Port of Riau Province based on ecological, social and technological dimensions. This research was carried out from February to March 2021 at the Fisheries Port Technical Implementation Unit (UPT) of Riau Province. This research used a survey method. The data collected related to the sustainability aspects of the sondong fishery includes the ecological, social and technological dimensions using a questionnaire. Analysis for the sustainability of the sondong fishery is based on ecological, social and technological aspects using the Rapid Appraisal for Fisheries (RAPFISH) method. RAPFISH (Rapid Appraisal for Fisheries) was developed by the Fisheries Center, University of British Columbia in 1999; Rapid Appraisal for Fisheries (RAPFISH) is a fisheries sustainability assessment method based on a multidimensional scaling approach. Dimensions in RAPFISH concern aspects of sustainability from ecology, economy, technology, social and ethics. The Multidimensional Sustainability Status of the Sondong Fishery is quite sustainable, with a score of 51.87. The ecological (53.58) and social (58.62) dimensions are quite sustainable, the technological dimension (45.80) is less sustainableKeyword :Survey,Status Of Sustainability, Sondong, Rapfish